Assessment of Drinking Water Quality through Physicochemical Analysis of Bore Well Samples in Mokokchung, Nagaland - Pranay Punj Pankaj; Rejuba Pongen; Nohochem Sangtam (The Bioscan, 2024)
This study investigates the water quality of bore wells in Mokokchung Municipality, Nagaland, India. Eleven wards were selected for sampling, and various physicochemical parameters were analyzed, including pH, turbidity, total dissolved solids (TDS), total hardness, calcium, magnesium, total alkalinity, chloride, iron, nitrate, fluoride, and dissolved oxygen (DO). The results were compared with guidelines from the World Health Organization (WHO) and the Bureau of Indian Standards (BIS). The findings indicate that all measured parameters fall within acceptable limits, suggesting that the bore well water in Mokokchung, Nagaland is suitable for domestic and drinking purposes. This study highlights the importance of regular water quality monitoring to ensure the safety and health of local populations.